Scavenging H2O2 of plant host by saliva catalase of leafhopper vector benefits viral transmission - Zhang, Hongxiang; Chi, Yunhua; Chen, Siyu; Lv, Xinwei; Jia, Dongsheng; Chen, Qian; Wei, Taiyun (The New phytologist, 2024)
Summary Catalase (CAT) is the main reactive oxygen species (ROS)‐scavenging enzyme in plants and insects. However, it remains elusive whether and how insect saliva CAT suppresses ROS‐mediated plant defense, thereby promoting initial virus transmission by insect vectors. Here, we investigated how leafhopper Recilia dorsalis catalase (RdCAT) was secreted from insect salivary glands into rice phloem, and how it was perceived by rice chaperone NO CATALASE ACTIVITY1 (OsNCA1) to scavenge excessive H2O2 during insect‐to‐plant virus transmission. We found that the interaction of OsNCA1 with RdCAT activated its enzymatic activity to decompose H2O2 in rice plants during leafhopper feeding. However, initial insect feeding did not significantly change rice CATs transcripts. Knockout of OsNCA1 in transgenic lines decreased leafhopper feeding‐activated CAT activity and caused higher H2O2 accumulation. A devastating rice reovirus activated RdCAT expression and promoted the cosecretion of virions and RdCAT into leafhopper salivary cavities and ultimately into the phloem. Virus‐mediated increase of RdCAT secretion suppressed excessive H2O2, thereby promoting host attractiveness to insect vectors and initial virus transmission. Our findings provide insights into how insect saliva CAT is secreted and perceived by plant chaperones to suppress the early H2O2 burst during insect feeding, thereby facilitating viral transmission.